2023
DOI: 10.1007/s10639-023-11882-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting students’ online courses learning behaviors

Abstract: Online course learning is an important part of higher education curriculum. However, the factors influencing college students’ online course learning behavior are poorly understood. The purpose of this study is to analyze the factors affecting college students’ online course learning behavior. This study integrated the Information System Success Model, the Technology Acceptance Model, and Self-efficacy Theory to construct an online course learning acceptance model. A total of 308 college students participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…Further, perceived VLE usability and ease of use are both important predictors of attitude toward VLE use [45]. According to studies [43,[45][46][47][48][49][50], perceived user-friendliness has a direct impact on how useful people perceive a VLE. Digital technology will only be viewed as useful by students if they find it convenient to use.…”
Section: Discussionmentioning
confidence: 99%
“…Further, perceived VLE usability and ease of use are both important predictors of attitude toward VLE use [45]. According to studies [43,[45][46][47][48][49][50], perceived user-friendliness has a direct impact on how useful people perceive a VLE. Digital technology will only be viewed as useful by students if they find it convenient to use.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, research on academicians in Saudi Arabia found that perceived ease of use was the most influential factor in shaping their attitudes towards e-learning [ 53 ]. Similarly, a study on Chinese college students found a positive relationship between perceived ease of use and attitudes towards online learning [ 54 ]. Further evidence found that perceived ease of use of digital tools positively impacted attitudes towards their use in higher education [ 55 ].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…The empirical acceptance of this model has led to its use in other fields, including those of education and business, and the combination of TAM with other exogenous variables has also been explored (Peng & Yan, 2022). It has also been demonstrated in the literature that PEOU and PU are significant extrinsic factors influencing students' behavioural intention (BI) and actual use (AU) of different instructional platforms like Zoom (Huang, 2023). TAM has established its credibility over the past few years as a trustworthy approach for gauging people's openness to adopting new technologies.…”
Section: Revisiting the Technology Acceptance Model And Hypotheses Fo...mentioning
confidence: 99%